Effects of tenebrio molitor linnaeus on degradation and conversion of food waste into organic fertilizer - Ng, Joseph. (2009)
The objectives of this project were to investigate the effects of Tenebrio Molitor Linnaeus (yellow mealworm), larvae of Tenebrio Molitor on degradation and conversion of food waste into organic fertilizer. There is a lack of literature review showing the conditions in which mealworms can live. Moisture content and pH are important to the survival of mealworms. In the study, a high survival rate of about 88.0% of the mealworms was observed at moisture content between 60% and 70% and pH between 6.0 and 8.5. The most significant effect of mealworms on degradation of food waste was the additional average mass reduction of 32.9% of the food waste contributed by the ingestion activity of mealworms in the 4 worm set-ups. Highest feeding rate of mealworms was observed to be 29.8 g/day. The highest carbon content reduction was observed in VBB4, with a reduction of 9.02% more than control 4. The average carbon content reduction in the mealworm set-ups was 15.22% lower compared to earthworm set-ups. Mealworm seemed to be more effective in the degradation of food waste through ingestion and less effective in the volatile solid (VS) and carbon content reduction. Three most important nutrients are nitrogen, phosphorus and potassium (NPK). In the conventional composting processes, loss of valuable nitrogen has always been a big issue of concern. However, there was an average increase in the nitrogen content of 20.64% in the 4 mealworm set-ups while there was an average loss in the nitrogen content of 13.95% in their 4 controls. Compared to earthworm set-ups, the increase in the average nitrogen content was 11.09% higher. In addition, the increments in the average phosphorus and potassium content in the 4 mealworm set-ups were 127.36% and 27.50% respectively. Compared to earthworm set-ups, the increments in the average phosphorus and potassium in the mealworm set-ups were 42.05% and 16.81% higher respectively. It was shown that mealworm casting had a higher percentage increase of NPK than earthworm casting. It can be concluded that mealworm casting could be used as fertilizers. Lastly, it was found that the addition of horticultural compost and wood residue as bulking agent could speed up degradation process and improve the stability index. Bioconversion period between 50 and 55 days was needed for the degradation process of food waste without bulking agents. However, bioconversion period of 30 days was achieved for the mixture of food waste and bulking agents to reach low stability. Mealworm castings were also mature and did not inhibit seed germination.